How significant are mandatory carbon and sustainability reporting requirements under the Renewable Transport Fuels Obligation (RTFO) in driving transport fuel suppliers to source more sustainable biofuels? - Bayly, Josh (2009)
As concern about climate change, resource scarcity and energy security grows among policy-makers and the transport fuel sector, biofuels have been held up as a means of diversifying fuel supplies and reducing carbon emissions. Biofuels are a renewable resource using agricultural feedstocks that absorb carbon dioxide as they grow, making them carbon neutral when combusted. Interest in biofuels led to the introduction of the EU Biofuels Directive, which requires member states to set targets for the inclusion of an escalating proportion of renewable fuels in transport fuels sold between 2008 and 2010/11; rising to 5% by 2010/11. The Renewable Transport Fuels Obligation (RTFO), administered by the Renewable Fuels Agency (RFA), is the UK’s implementation of the Directive.